Molecularly Resonant Metamaterials for Broad‐Band Electromagnetic Stealth - Yifan Wang; Jiarong Niu; Xin Jin; Xiaoming Qian; Changfa Xiao; Wenyu Wang (Advanced Science, 2023)
Abstract Electromagnetic (EM) metamaterial is a composite material with EM stealth properties, which is constructed by artificially reverse engineering metal split resonance rings (SRR). However, the greatest limitation of EM metamaterials is that they can only stealth at a fixed and lower frequency of EM waves, and modern processing techniques still cannot meet the accuracy requirements to fabric nano‐size structural unit. Nano‐sized and even ultra‐small SRR at molecular level are promising arrays to realize the ability of EM stealth function at a higher frequency, although it has proven challenging to synthesize long, straight, connected molecular SRR, and also difficult to arrange those molecular SRR into a strict array. Here, the study overcomes this challenge and demonstrates that the fabric of polypyrrole molecular SRR achieves an ultra‐small inner diameter of 2.49 Å and realizes the arrays arrangement at molecular level. Furthermore, the study exploits the EM stealth function and verifies that such arrays of molecular SRR with 2.49 Å have the ability to reach high‐performance EM stealth in the range of 106–1016 Hz. This design concept opens a pathway for developing new metamaterials with broadband EM wave stealth and also serves the wider range of new applications.